Pre- and Post-Local Anesthesia Hemodynamics in Patients with Ophthalmology Surgery - Ni Luh Putu Lusiana Devi; I Ketut Setiabudi; I Gusti Agung Tresna Wicaksana; Luh Gde Nita Sri Wahyuningsih (PROMOTOR, 2024)
Effective and safe anesthesia in eye surgery is essential to ensure optimal perioperative care for both children and adults, so hemodynamic monitoring is essential. The use of local anesthesia can increase systolic blood pressure and diastolic blood pressure without changing heart rate. A quantitative descriptive study with a cross-sectional approach involved 138 patients with purposive sampling techniques. Univariate analysis with frequency distribution was used in this study. The results showed that pre-anesthetic systolic TD ≥ 147 mmHg as much as 56%, pre-anesthesia diastolic TD < 78 mmHg as much as 51%, MAP ≥ 101 mmHg as much as 54%, and heart rate < 79 x / minute. While systolic TD after anesthesia ≥ 147 mmHg as much as 59%, diastolic TD ≥ 78 mmHg as much as 62%, MAP ≥ 101 mmHg as much as 64%, and heart rate < 79 x / minute as much as 58%. Changes in systolic and diastolic blood pressure were found in pre and post-anesthesia, so more detailed monitoring is needed.